Assessment on bacteria in the heavy metal bioremediation - Osman, Mohamad Romizan; Azid, Azman; Yunus, Kamaruzzaman; Mustafa, Ahmad Dasuki; Amran, Mohammad Azizi; Azaman, Fazureen; Suhaili, Zarizal; Abu Bakar, Yahya; Mohamed Zainuddin, Syahrir Farihan (Universiti Kebangsaan Malaysia (UKM), 2015)
The aim of this study was to identify and verify the potential bacteria as the bioremediation agent. It involved bacteria isolation, identification through Gram staining, analytical profile index (API) test and determine bioremediation activities by using inductively coupled plasma mass spectrometry (ICPMS). The soil and water sample were collected from downstream of Galing River, Kuantan Malaysia. Based on phenotypic identification and iochemical analysis, the bacteria present at the vicinity area are possibility of Myroides spp. and Micrococcus spp. These bacteria were proven as bioremediation agent based on the ICPMS result. The result 1 ppm of Zink (Zn), Lead (Pb), Arsenic (As), Selenium (Se), Cadmium (Cd), Manganese (Mn), and Indium (In) dwindled after the bacteria inoculated and incubated for seven days in mixture of base salt media (BSM) with the heavy metal elements. Therefore, this proves that the bacteria which are present at downstream of Galing River, Kuantan Malaysia are significant to help us in the bioremediation activity to decrease the heavy metal pollution in the environment.